Assuring Access to Safe Medicines in Pregnancy and Breastfeeding. Issue 4 (1st May 2021) - Nooney, Janet; Thor, Shannon; de Vries, Corinne; Clements, John; Sahin, Leyla; Hua, Wei; Everett, Darcie; Zaccaria, Cosimo; Ball, Robert; Saint‐Raymond, Agnes; Yao, Lynne; Raine, June; et al.
Abstract : Scientists and regulators in Europe and the United States continue to seek methods and strategies to improve knowledge on rational use of medicines for pregnant and breastfeeding populations, an important subset of women's health. Regulatory agencies have made strides toward improvement, but much more is needed. Recognizing the importance of international collaboration, we have begun to consider how to address these important public health issues more globally. The health of the child begins with the health of the mother.